THE EFFECT OF INSULIN LIKE GROWTH FACTOR – I COMPLEX TO CORELATION MALONDIALDEHIDE CONCENTRATE WITH INTAC MEMBRAN PLASMA OF SPERM - Susilowati, Suherni (Jurnal Veteriner, 2008)
The aim of this research was study of Insulin Like Growth -I Complex to level of malondialdehide (MDA) and percentage of intact membrane plasm. Report of several species suggest that seminal plasma contains factors that may influence sperm viability. Seminal plasma was reported to be important for maintaining spermatozoa motility in bull and ram. For improving ram sperm viability and for increasing the resistance of boar spermatozoa to cold shock damage. IGF-I has been identified in the testis, where secreted by Leydig and Sertoli cells. Collection of semen by using artificial vagina from male goats and then characterized of motility and viability of spermatozoa. Identification of Insulin Like Growth Factor –I Complex were done by Native-PAGE 12% techniques, after several bands were identified and was done isolate of first band protein Insulin Like Growth Factor-I Complex. Insulin Like Growth Factor – I (IGF-I) Complex seminal plasma have molecular weight of 150,288 kDa, respectively. Sperm preparation for this research by centrifugation of semen with Bracket and Oliphan’s medium. These sperm preparation were characterized of motility, viability. Then after sperm preparation divided into three groups. The group I, added with Bracket and Oliphan’t medium, group II added with Bracket Oliphan’t and IGF – I Complex medium, group III added with IGF – I Complex medium and then were exposed 45 minutes for incubation and then percentage of MPU and level of MDA was evaluated. The result of this research showed that percentage of level MDA has significant different between group I,group II and group III, (p<0,05). The percentage of MPU sperm has significant different between groups I, group II and group III (p<0,05). The highest of percentage MPU was found in group III and the lower of level MDA was found in group III. Regresion test showed that negative correlation between level of MDA and percentage of MPU sperm.
Keywords: Seminal plasma, IGF-I Complex, MDA and MPU